Efficient State Update Exchange in a CPS Environment for Linked Data-based Digital Twins - Berezovskyi, Andrii; Inam, Rafia; El-khoury, Jad; Torngren, Martin; Fersman, Elena (IEEE International Conference on Industrial Informatics (INDIN), 2019)
This paper addresses the problem of reducing the number of messages needed to exchange state updates between the Cyber-Physical System (CPS) components that integrate with the rest of the CPS through Digital Twins in order to maintain uniform communication interface and carry out their tasks correctly and safely. The main contribution is a proposed architecture and the discussion of its suitability to support correct execution of complex tasks across the CPS. A new State Event Filtering component is presented to provide event-based communication among Digital Twins that are based on the Linked Data principles while keeping the fan-out limited to ensure the scalability of the architecture.